Hydrogeology and hidrogeochemical modeling in phreatic aquifer of NE Mendoza, Argentina - Gomez, María Laura; Aranibar, Julieta; Wuilloud, Rodolfo; Rubio, Cecilia; Martínez, Daniel; Soria, Darío; Monasterio, Romina; Villagra, Pablo; Goirán, Silvana (Journal of Iberian Geology, 2014)
The objectives of this study are to develop a conceptual hydrogeological model and evaluate groundwater hydrochemical characteristics of the aquifer in the Guanacache Travesía, in the central Monte desert of Mendoza (Argentina). The region has been granted to aboriginal communities for communal use and is experiencing economic development. The area has limited surface water resources and relies on groundwater for economic activities, and in many cases, for human consumption. There are no hydrogeochemical studies on the quality of this water as drinking water or its suitability for agriculture and raising livestock. The present study provides information on water quality and availability in the northeast of Mendoza Province. It includes a detailed review of relevant bibliography, including scattered and unpublished studies with geological and geomorphological data. It also includes water level measurements, a definition of water flow direction and hydrochemical analyses, including some trace elements and isotopic data. The hydrogeological model shows a discharge area characterized by vertical upward flows, evident by thermal waters, lakes, salt deposits and the presence of reduced arsenic in some boreholes. The dominance of fine sediments, low relief, scarce local precipitation, low recharge from precipitation, and low groundwater velocities result in long residence times for groundwater and poor renovation (with remote recharge area). Groundwater has high salt content and hardness, as well as trace elements such as fluoride and arsenic. Localized patches of low salinity waters are found along paleochannels. The isotopic signature of these waters indicates distant precipitation from the mountains, which could also have recharged the aquifer in historic times. In addition to the important geologic controls on surface and groundwater flows, human activities affect local conditions of the aquifer near livestock gathering areas, increasing nitrate concentrations and the proportion of As(III) relative to As(V).